Highly sulfiphilic Ni-Fe bimetallic oxide nanoparticles anchored on carbon nanotubes enable effective immobilization and conversion of polysulfides for stable lithium-sulfur batteries. (February 2019) - Zhang, Ze; Basu, Swastik; Zhu, Peipei; Zhang, Hai; Shao, Ahu; Koratkar, Nikhil; Yang, Zhenyu
Abstract: Deficiencies of sulfur cathode including polysulfide shuttling and poor redox kinetics severely limit cycling performance of lithium-sulfur (Li-S) batteries. Herein, we have designed a binary host featuring highly sulfiphilic Ni-Fe bimetallic oxide (NiFe2 O4 ) nanoparticles anchored on carbon nanotubes for Li-S batteries. NiFe2 O4 nanoparticles provide highly sulfiphilic sites to confine lithium polysulfides by the formation of Li-O and S-O bonds, and act as an electrocatalyst to promote the conversion of polysulfides. The carbon nanotubes play an important synergistic role by providing efficient electron conduction pathways and preventing agglomeration of the catalyst. As a result, the sulfur cathode enables stable cycling with a very low capacity fade rate (∼0.029% per cycle upon 1000 cycles) at 1.0 C and a reversible capacity of ∼550 mAh g −1 at 5.0 C. Further, the superior cycling stability could be retained even for high sulfur loading of ∼5.0 mg cm −2 . The development of such hybrid electrodes comprised of bimetallic oxides supported on carbon nanotubes could help realize long-lasting and stable Li–S batteries. Graphical abstract: Ni-Fe bimetallic oxide nanoparticles anchored on carbon nanotube supports are reported to show highly sulfiphilic sites for polysulfide immobilization and the conversion of polysulfides/sulfides for long-lasting and stable lithium-sulfur batteries. Image 1